Pengaruh Disiplin dan Motivasi Terhadap Kinerja Karyawan Divisi Operasional PT. Sankyu Indonesia International - Suharno Suharno; Cecep Warman (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research was conducted to determine the influence of discipline and motivation on employee performance in the Operational Division of PT Sankyu Indonesia International. The research method used in this research is a quantitative approach with data collection techniques through questionnaires. The sampling technique used a saturated sampling technique, the sample was 36 people who worked as employees of the Operational Division of PT Sankyu Indonesia International. The results of the descriptive analysis show that the influence of discipline and motivation on employee performance in the Operational Division of PT Sankyu Indonesia International is classified as very good, where the three variables are in the rating scale range of 70-100. From the results of the hypothesis test, it shows that discipline has a positive and significant effect on employee performance. The results of the analysis have a significance value of 0.000 and t count 4.125 > t table 1.68830. Motivation does not have a positive effect on employee performance as a result of the analysis with a significance value of 0.427 and t count 0.804 < t table 1.68830. Discipline and Motivation simultaneously have a positive and significant effect on Employee Performance, the results of the analysis have a significance value of 0.000 and F count 9.970 > F table 3.26.